2008
DOI: 10.1016/j.jcv.2008.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection and typing of influenza viruses: Are we ready for an influenza pandemic?

Abstract: These data suggest that improvements are needed in the molecular detection of influenza viruses and influenza virus A haemagglutinin subtyping. Only rapid and accurate identification of circulating pandemic influenza virus will ensure that the maximum time is available for intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…The importance of proficiency testing as learning tool for improving sensitivity and specificity of molecular diagnostics in relation to seasonal influenza and avian influenza A(H5N1) has been demonstrated before. 8,13,14 Therefore, following communication of the first results of the proficiency panel to the OAL network, most laboratories took action to improve the assays using the CDC primers and probes sets in addition to the in-house influenza A virus detection assays. Our comparative evaluation clearly illustrates one of the challenges in implementing (molecular) diagnostics for a new pathogen, namely the lack of standardisation of these techniques among laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of proficiency testing as learning tool for improving sensitivity and specificity of molecular diagnostics in relation to seasonal influenza and avian influenza A(H5N1) has been demonstrated before. 8,13,14 Therefore, following communication of the first results of the proficiency panel to the OAL network, most laboratories took action to improve the assays using the CDC primers and probes sets in addition to the in-house influenza A virus detection assays. Our comparative evaluation clearly illustrates one of the challenges in implementing (molecular) diagnostics for a new pathogen, namely the lack of standardisation of these techniques among laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…7 Therefore, the most likely scenario would be that other laboratories start testing as well but without the proper preparation which could lead to incorrect diagnoses, given the relatively poor performance in quality control exercises for emerging diseases. 25,26 Therefore, we conclude that a discussion is needed on how the use of diagnostic capacity can be further maximized by triage criteria for diagnostics of community cases of acute respiratory infections in close collaboration with public health officials. If illness in the general community (presenting to GPs) caused by a new pandemic influenza virus cannot be distinguished clinically from other respiratory diseases, the demand for laboratory diagnostics can rapidly increase.…”
Section: Discussionmentioning
confidence: 99%
“…Despite considerable progress in treatment, influenza remains an uncontrolled global infection with unpredictable morbidity and mortality rates. In the last two or three decades, the dominating viruses of influenza epidemics belonged to serotype A, whereas recent years have witnessed epidemic episodes caused by viruses of both the A and B serotypes (3,7,17). Influenza virus A (H5N1) circulating in birds is a menace to humans and (23).…”
Section: Discussionmentioning
confidence: 99%
“…The spectrum of drugs inhibiting the pathogen is limited. Recent studies of avian influenza A H5N1, H7N7, and H9N2 viruses and of the H1N1 swine flu virus showed that the mutability of viruses is very high and that they can overcome interspecies barriers and infect humans (7,17,22,23). These facts stimulated intensive studies of new agents capable of inhibiting influenza viruses of different origins (1,10,12,21,22,27).…”
Section: Influenza Viruses Of Typesmentioning
confidence: 99%